Liquid crystal alignment agent for vertical alignment, liquid crystal alignment film, and liquid crystal display element
Patent Information
- Application Number
- JP2024126161
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-24
- Filing Date
- 2024-08-01
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-09-23
AI Technical Summary
【0010】 本発明によれば、高い屈折率を有しながらも着色性を有しないために高い光透過率を有する液晶配向膜を形成する垂直配向(VA)用の液晶配向剤が得られる。かかる液晶配向剤が形成される液晶配向膜は、高い屈折率を有するために、液晶表示素子における透明導電膜の屈折率と液晶配向膜の屈折率との差を小さくすることができ、また、着色性を有しないために、光の透過率が高く、かつ表示輝度の高い、垂直配向(VA)方式の液晶表示素子を得ることができる。
Smart Images

Figure 0007635878000001 
Figure 0007635878000002 
Figure 0007635878000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystal aligning agent for vertical alignment (VA), a liquid crystal alignment film obtained from the liquid crystal aligning agent, a liquid crystal display element having the liquid crystal alignment film, and novel diamines and polymers suitable therefor. [Background technology]
[0002] Liquid crystal display elements are widely used in a wide range of applications, from small applications such as mobile phones and smartphones to relatively large applications such as televisions and monitors. Liquid crystal display elements are generally constructed by arranging a pair of electrode substrates facing each other with a predetermined gap (several μm) between them and sealing liquid crystal between the electrode substrates. Display on the liquid crystal display element is performed by applying a voltage between the transparent conductive films constituting the electrodes of the electrode substrates. These liquid crystal display elements have a liquid crystal alignment film that is essential for controlling the alignment state of liquid crystal molecules.
[0003] Meanwhile, various driving methods have been developed for liquid crystal display elements, which differ in electrode structure, physical properties of the liquid crystal molecules used, etc. For example, various modes such as the Twisted Nematic (TN) method, the Super Twisted Nematic (STN) method, the Vertical Alignment (VA) method, the In-Plane Switching (IPS) method, and the FFS (fringe field switching) method are known. In particular, VA (vertical alignment) type liquid crystal display elements have a wide viewing angle, fast response speed, high contrast, and do not require rubbing processing in the production process, so they are widely used, especially in televisions and monitors, where there is a high demand for larger displays. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2008 / 117615 [Patent Document 2] Japanese Patent Publication No. 2008-76950 Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, the above-mentioned transparent conductive film in a liquid crystal display element is usually formed of a composition (ITO) in which indium oxide is the main component and is doped with a few percent of tin oxide, and the refractive index of the film is different from that of the liquid crystal alignment film and has a high value. Therefore, when light from a display light source is transmitted through the electrode substrate, the light is reflected at the interface between the transparent conductive film and the liquid crystal alignment film in each electrode substrate. As a result, the light transmittance of the electrode substrate cannot be sufficiently obtained, leading to a problem of a decrease in display brightness. In particular, ultra-high definition panels such as 4K and 8K have been developed in recent years, but these panels require a large occupancy rate of black matrix (BM) and TFT, etc., which reduces the aperture ratio of the panel, so improving the transmittance of the display area is becoming important.
[0006] Therefore, the present inventors have investigated various materials for forming the liquid crystal alignment film in order to increase the refractive index of the liquid crystal alignment film, from the viewpoint that the above-mentioned problems can be solved by reducing the difference between the refractive index of the transparent conductive film and the refractive index of the liquid crystal alignment film. Specifically, in order to increase the refractive index of the liquid crystal alignment film, various types of polymers to be contained in the liquid crystal alignment agent forming the liquid crystal alignment film have been searched for.
[0007] As a result, by selecting a specific polymer, it was possible to obtain a liquid crystal alignment film having a refractive index close to that of the transparent conductive film, but on the other hand, it was revealed that the polymer forming the liquid crystal alignment film having a high refractive index often has coloring properties. A liquid crystal alignment film formed from a liquid crystal alignment agent containing a polymer having coloring properties has low light transmittance, which leads to a decrease in display brightness, and as a result, the above-mentioned object is not achieved.
[0008] In view of the above circumstances, the object of the present invention is to provide a liquid crystal alignment agent that forms a liquid crystal alignment film for VA (vertical alignment) having a high refractive index while not being colored and therefore having a high light transmittance, a liquid crystal alignment film obtained from the liquid crystal alignment agent, and a liquid crystal display element having the liquid crystal alignment film. [Means for solving the problem]
[0009] As a result of intensive research into achieving the above object, the present inventors have found that a liquid crystal aligning agent containing a partially novel polymer having a specific structure is effective for achieving the above object, and have completed the present invention. The present invention relates to a liquid crystal alignment agent for vertical alignment (VA), characterized by containing at least one polymer (P) selected from the group consisting of a polyimide precursor obtained by using a diamine component containing a diamine (0) represented by the following formula (0) and a polyimide which is an imidized product of the polyimide precursor; a liquid crystal alignment film obtained from the liquid crystal alignment agent; and a vertical alignment type liquid crystal display element having the liquid crystal alignment film. [ka] (A and A' each independently represent a monocyclic group, a fused ring group, or a group in which two of the monocyclic groups are bonded together, and at least one of A and A' represents a fused ring group. L represents a single bond or -X 1 -QX 2 - represents a group. 1 and X 2 each independently represents a single bond, an oxygen atom, or a sulfur atom; and Q represents an alkylene group having 1 or 2 carbon atoms. Effect of the Invention
[0010] According to the present invention, a liquid crystal alignment agent for vertical alignment (VA) is obtained, which has a high refractive index but is not colored, and thus forms a liquid crystal alignment film with high light transmittance. Since the liquid crystal alignment film on which such a liquid crystal alignment agent is formed has a high refractive index, the difference between the refractive index of the transparent conductive film in a liquid crystal display element and the refractive index of the liquid crystal alignment film can be reduced, and since it is not colored, a vertical alignment (VA) type liquid crystal display element with high light transmittance and high display brightness can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] As described above, the liquid crystal alignment agent of the present invention is characterized in that it contains at least one polymer (P) selected from the group consisting of polyimide precursors obtained by using a diamine component containing diamine (0) represented by the following formula (0) and polyimides which are imidized products of the polyimide precursors. [ka] In the above formula (0), A, A', L, X 1 , X 2 are as defined above.
[0012] The monocyclic group in A and A' refers to a divalent group obtained by removing two hydrogen atoms from a monocyclic ring. Examples of the monocyclic ring include benzene; 5-membered heterocyclic rings such as furan, thiophene, pyrrole, oxazole, thiazole, imidazole, and pyrazole; and 6-membered heterocyclic rings such as pyran, pyrone, pyridine, pyridazine, pyrimidine, and pyrazine. The monocyclic ring is preferably benzene or pyridine. When the monocyclic ring is benzene, the monocyclic group is a phenylene group.
[0013] The fused ring group in A and A' refers to a divalent group obtained by removing two hydrogen atoms from a fused ring. Examples of the fused ring include fused polycyclic aromatic hydrocarbons such as naphthalene, tetralin, indene, fluorene, anthracene, phenanthrene, and pyrene; and fused polycyclic heterocycles such as benzofuran, thionaphthene, indole, carbazole, coumarin, benzo-pyrone, quinoline, isoquinoline, acridine, phthalazine, quinazoline, and quinoxaline. The fused ring is preferably naphthalene, anthracene, pyrene, indole, carbazole, coumarin, benzo-pyrone, quinoline, or isoquinoline. The group having two monocyclic groups bonded thereto is preferably a biphenyl structure or a bipyridine group.
[0014] Among these, from the viewpoint of obtaining the effects of the present invention, A and A' are preferably a phenylene group, a pyridinyl group, a naphthylene group, an anthracenyl group, a quinolinyl group, a biphenyl structure, or a bipyridinyl group. L is a single bond, -O-(CH 2 ) n - (n is an integer of 1 or 2), or -O-(CH 2 ) n -O- (n is an integer of 1 or 2) is preferred. Specific examples of the diamine (0) represented by the above formula (0) include the following formulae (d-1) to (d-21).
[0015] [ka] [ka]
[0016] A preferred specific example of the diamine (0) represented by the above formula (0) is a diamine represented by the following formula (1). [ka] In the above formula (1), A, L, and X 1 , X 2are as defined above.
[0017] Preferred specific examples of the diamine (1) represented by the above formula (1) include the formulas (d-1) to (d-7), (d-13) to (d-14), (d-17) to (d-18), and (d-21) among the above formulas (d-1) to (d-21).
[0018] The polymer (P) contained in the liquid crystal alignment agent of the present invention is preferably at least one polymer selected from the group consisting of polyimide precursors obtained by using a diamine component containing, in addition to the diamine represented by the above formula (0), at least one diamine (s) having structures represented by the following formulae (S1) to (S3), and polyimides which are imidized products of the polyimide precursors. [ka]
[0019] In formula [S1], X 1 and X 2 are each independently a single bond, -(CH 2 ) a -(a is an integer from 1 to 15), -CONH-, -NHCO-, -CON(CH 3 )-, -NH-, -O-, -COO-, -OCO- or -((CH 2 ) a1 -A 1 ) m1 -(a1 is an integer from 1 to 15, A 1 represents an oxygen atom or -COO-, m 1 is an integer between 1 and 2. 1 If is 2, multiple a1 and A 1 Each of G and G independently has the same definition as above. 1 and G 2each independently represents a divalent cyclic group selected from a divalent aromatic group having 6 to 12 carbon atoms and a divalent alicyclic group having 3 to 8 carbon atoms. Any hydrogen atom on the cyclic group may be substituted with an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorine-containing alkyl group having 1 to 3 carbon atoms, a fluorine-containing alkoxy group having 1 to 3 carbon atoms, or a fluorine atom. each independently represents an integer of 0 to 3, and the sum of m and n is 1 to 6, preferably 1 to 4. R 1 represents an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms; R 1 Any hydrogen atom forming the formula (I) may be substituted with a fluorine atom. Also, G 1 , G 2 Examples of the divalent cyclic group in the formula (I) include a cyclopropylene group, a cyclohexylene group, and a phenylene group. Any hydrogen atom on these cyclic groups may be substituted with an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorine-containing alkyl group having 1 to 3 carbon atoms, a fluorine-containing alkoxy group having 1 to 3 carbon atoms, or a fluorine atom.
[0020] [ka] In formula [S2], X 3 is a single bond, -CONH-, -NHCO-, -CON(CH 3 )-, -NH-, -O-, -CH 2 R represents -O-, -COO- or -OCO-. 2 represents an alkyl group having 1 to 20 carbon atoms or an alkoxyalkyl group having 2 to 20 carbon atoms; R 2 Any hydrogen atom forming the formula (I) may be substituted with a fluorine atom. Also, R 2 From the viewpoint of improving the liquid crystal alignment property, the alkyl group having 3 to 20 carbon atoms or an alkoxyalkyl group having 2 to 20 carbon atoms is preferable.
[0021] [ka] In formula [S3], X 4 -CONH-, -NHCO-, -O-, -CH 2 O-, -OCH 2 -, -COO- or -OCO-. 3 represents a structure having a steroid skeleton. 3 is preferably a structure containing a cholestanyl group, a cholesteryl group or a lanostannyl group.
[0022] Preferred specific examples of formula [S1] include the following formulae [S1-x1] to [S1-x7]. [ka]
[0023] In the above formula, R 1 X is an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms. p is -(CH 2 ) a -(a is an integer from 1 to 15), -CONH-, -NHCO-, -CON(CH 3 )-, -NH-, -O-, -CH 2 O-, -CH 2 It is OCO-, -COO-, or -OCO-. 1 is an oxygen atom or -COO-* (where the bond marked with "*" is (CH 2 ) a2 (combines with), A 2 is an oxygen atom *-COO- (where the bond marked with "*" is (CH 2 ) a2 ) and a 3 is 0 or 1, a 1 , a 2 are each independently an integer of 1 to 10, and Cy is a 1,4-cyclohexylene group or a 1,4-phenylene group. Preferred examples of the formula [S2] include X 3 But -O-, -CH 2 R is either -O-, -COO- or -OCO-; 2is preferably an alkyl group having 3 to 20 carbon atoms or an alkoxyalkyl group having 2 to 20 carbon atoms, and R 2 is more preferably an alkyl group having 3 to 20 carbon atoms, and R 2 Any hydrogen atom forming the formula (I) may be substituted with a fluorine atom.
[0024] A preferred specific example of the above formula [S3] is the following formula [S3-x]. In the formula [S3-x], X is the formula [X1], the formula [X2] or the formula [X3], Col is the formula [Col1], the formula [Col2] or the formula [Col3], and G is the formula [G1], the formula [G2], the formula [G3] or the formula [G4]. Me represents a methyl group.
[0025] [ka]
[0026] Preferred diamines (s) having the structures represented by the above formulas (S1) to (S3) include diamines represented by the following formula (d1) or formula (d2). [ka]
[0027] In formulae (d1) and (d2), Y represents a side chain structure represented by the above formulae [S1] to [S3], and the two Y's in formula (d2) may be the same or different. X represents a single bond, -O-, -C(CH 3 ) 2 -, -NH-, -CO-, -(CH 2 ) m -, -SO 2 -, -O-(CH 2 ) m -O-, -OC(CH 3 ) 2 -, -CO-(CH 2 ) m -, -NH-(CH 2 ) m -, -SO 2 -(CH 2 ) m-,-CONH-(CH 2 ) m -,-CONH-(CH 2 ) m -NHCO-, -COO-(CH 2 ) m -OCO-, -COO-, -CONH-, -NH-(CH 2 ) m -NH-, -SO 2 -(CH 2 ) m -SO 2 m is an integer from 1 to 8.
[0028] Preferred specific examples of the diamine of the above formula (d1) include the following formulas (d1-1) to (d1-18). [ka] (n is an integer from 1 to 20.)
[0029] [ka]
[0030] The diamine represented by the above formula (d2) may have a structure selected from the group consisting of the following formulae (d2-1) to (d2-6). [ka]
[0031] In the above formula, X p1 ~X p8 Each independently represents X in the above formulas [S1-x1] to [S1-x6]. p is synonymous with X s1 ~X s4 are each independently -O-, -CH 2 O-, -OCH 2 -, -COO- or -OCO-, X a ~X f -O-, -NH-, -O-(CH 2 ) m -O-, -C(CH3 ) 2 -, -CO-, -COO-, -CONH-, -(CH 2 ) m -, -SO 2 -, -OC(CH 3 ) 2 -, -CO-(CH 2 ) m -, -NH-(CH 2 ) m -, -NH-(CH 2 ) m -NH-, -SO 2 -(CH 2 ) m -, -SO 2 -(CH 2 ) m -SO 2 -,-CONH-(CH 2 ) m -,-CONH-(CH 2 ) m -NHCO- or -COO-(CH 2 ) m -OCO- indicates R 1a ~R 1h each independently represents an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms. m is an integer of 1 to 8.
[0032] (Production of Polymer (P)) The polymer (P) contained in the liquid crystal alignment agent of the present invention is a polyimide precursor obtained by using a diamine component containing the above diamine (0), preferably a diamine component containing diamine (s) in addition to the above diamine (0), or a polyimide which is an imidized product of the polyimide precursor. Here, the polyimide precursor is a polymer from which a polyimide can be obtained by imidizing a polyamic acid, a polyamic acid ester, or the like.
[0033] The polyamic acid (P), which is a polyimide precursor of the polymer (P), can be obtained by a polymerization reaction between a diamine component containing the diamine (0) described above, preferably a diamine component containing diamine (s) in addition to the diamine (0), and a tetracarboxylic acid component. In this case, the amount of diamine (0) used is preferably from 1 to 100 mol %, more preferably from 1 to 99 mol %, and even more preferably from 5 to 95 mol %, based on the diamine component to be reacted with the tetracarboxylic acid component.
[0034] When diamine (s) is used in addition to the diamine (0), the amount of diamine (s) used is preferably 1 to 99 mol %, more preferably 1 to 95 mol %, based on the diamine component to be reacted with the tetracarboxylic acid component.
[0035] The diamine component used in the production of the polyamic acid (P) may contain diamines other than the diamine (0) and the diamine (s) (hereinafter, these are also referred to as other diamines). Examples of other diamines are given below, but the present invention is not limited thereto.
[0036] Diamines having a carboxy group such as p-phenylenediamine, m-phenylenediamine, 4-(2-(methylamino)ethyl)aniline, and 3,5-diaminobenzoic acid, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenylether, 3,3'-diaminodiphenylether, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 1,2-bis(4-aminophenyl)ethane, 1,3-bis(4-aminophenyl)propane, and 1,4-bis(4-amino phenyl)butane, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,2-bis(4-aminophenoxy)ethane, 1,2-bis(4-amino-2-methylphenoxy)ethane, 1,3-bis(4-aminophenoxy)propane, 1,4-bis(4-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)pentane, 1,6-bis(4-aminophenoxy)hexane, 4-(2-(4-aminophenoxy)ethoxy)-3-fluoroaniline, di(2-(4-amino phenoxy)ethyl) ether, 4-amino-4'-(2-(4-aminophenoxy)ethoxy)biphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 1,4-diaminonaphthalene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,7-diaminonaphthalene, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(4-amino diamines having a urea bond such as 1,3-bis(4-aminophenethyl)urea, diamines represented by the following formulas (a-1) to (a-6), preferably diamines having a photopolymerizable group at the terminal such as 2-(2,4-diaminophenoxy)ethyl methacrylate and 2,4-diamino-N,N-diallylaniline, diamines having a radical initiation function such as those represented by the following formulas (R1) to (R5), 2,6-diaminopyridine, 3,4-diaminopyridine, 2,4-diaminopyrimidine, 3,6-diaminocarbazole, N-methyl-3,6-diaminocarbazole, diamines having a heterocycle such as those represented by the following formulae (z-1) to (z-18), diamines having a diphenylamine skeleton such as those represented by the following formulae (Dp-1) to (Dp-3), organosiloxane-containing diamines such as 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, diamines having the group "-N(D)-" (D represents a protecting group that is eliminated by heating and replaced with a hydrogen atom, preferably a tert-butoxycarbonyl group) such as those represented by the following formulae (5-1) to (5-11), diamines having an oxazoline structure such as those represented by the following formulae (Ox-1) to (Ox-2), and diamines described in International Publication No. WO 2016 / 125870. [ka] [ka] [ka] (d1 represents an integer from 2 to 10.) [ka] (n represents an integer from 2 to 10.) [ka] [ka] (Boc represents a tert-butoxycarbonyl group.) [ka]
[0037] Among these, from the viewpoint of suitably obtaining the effects of the present invention, the other diamines preferably include p-phenylenediamine, 3,5-diaminobenzoic acid, 4,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2-(2,4-diaminophenoxy)ethyl methacrylate, 2,4-diamino-N,N-diallylaniline, diamines represented by the above formulae (R1) to (R5), diamines represented by the above formulae (z-1) to (z-18), diamines represented by the above formulae (5-1) to (5-11), and diamines represented by the above formulae (Ox-1) to (Ox-2). When other diamines are used in addition to the diamine (0), the amount of the other diamines used is preferably 1 to 99 mol %, more preferably 5 to 95 mol %, based on the total diamine components used. When other diamines are used in addition to the diamine (0) and diamine (s), the amount of diamine (s) used is preferably 98 mol % or less, more preferably 94 mol % or less, based on the diamine components to be reacted with the tetracarboxylic acid component.
[0038] The amount of the other diamines used is preferably 5 to 40 mol %, more preferably 10 to 40 mol %, based on the total diamine components used in the production of the polyamic acid (P).
[0039] In liquid crystal display elements using the PSA system or SC-PVA mode, from the viewpoint of increasing the response speed, one or more of 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, diamines having a photopolymerizable group at an end, diamines represented by the above formulae (R1) to (R5), and diamines represented by the above formulae (z-1) to (z-18) can be used when producing the polyamic acid (P), and the amount used is preferably 1 to 40 mol %, more preferably 5 to 40 mol %, based on the total diamine components used in the production of the polyamic acid (P).
[0040] (Tetracarboxylic acid component) When producing the above polyamic acid (P), the tetracarboxylic acid component to be reacted with the diamine component may be not only a tetracarboxylic acid dianhydride but also a derivative of a tetracarboxylic acid dianhydride such as a tetracarboxylic acid, a tetracarboxylic acid dihalide, a tetracarboxylic acid dialkyl ester, or a tetracarboxylic acid dialkyl ester dihalide.
[0041] The tetracarboxylic dianhydride or derivative thereof may be an aromatic tetracarboxylic dianhydride, an aliphatic tetracarboxylic dianhydride, an alicyclic tetracarboxylic dianhydride, or a derivative thereof. Here, the aromatic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxy groups including at least one carboxy group bonded to an aromatic ring. The aliphatic tetracarboxylic dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxy groups bonded to a chain hydrocarbon structure. However, it is not necessary for the structure to be composed only of a chain hydrocarbon structure, and it may have an alicyclic structure or an aromatic ring structure as a part of it.
[0042] In addition, an alicyclic tetracarboxylic acid dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxy groups, including at least one carboxy group bonded to an alicyclic structure. However, none of these four carboxy groups are bonded to an aromatic ring. In addition, it is not necessary for the alicyclic structure to be composed only of an alicyclic structure, and it may have a chain hydrocarbon structure or an aromatic ring structure as a part of the alicyclic structure.
[0043] Among them, the tetracarboxylic dianhydride or a derivative thereof is preferably one represented by the following formula (T). [ka] In the formula (T), X represents a structure selected from the group consisting of the following (x-1) to (x-13):
[0044] [ka]
[0045] In the above formula (x-1), R 1 ~R 4 R each independently represents a hydrogen atom, a methyl group, an ethyl group, a propyl group, a chlorine atom, or a phenyl group. 5 and R 6 Each of j and k independently represents a hydrogen atom or a methyl group. 1 and A 2 are each independently a single bond, an ether (-O-), a carbonyl (-CO-), an ester (-COO-), a phenylene, a sulfonyl group (-SO 2 -) or amide group (-CONH-), and two A 2 may be the same or different. *1 is a bond bonded to one acid anhydride group, and *2 is a bond bonded to the other acid anhydride group.
[0046] Preferred specific examples of the above formulae (x-12) and (x-13) include the following formulae (x-14) to (x-29), in which * represents a bond. [ka] [ka]
[0047] Preferred specific examples of the tetracarboxylic dianhydride or derivative thereof represented by the above formula (T) include those in which X is selected from the above formulas (x-1) to (x-7) and (x-11) to (x-13).
[0048] The proportion of the tetracarboxylic dianhydride represented by the above formula (T) or a derivative thereof used is preferably 1 mol % or more, more preferably 5 mol % or more, and even more preferably 10 mol % or more, based on 1 mol of the total tetracarboxylic acid components used. The tetracarboxylic dianhydride and its derivatives used in the production of the polyamic acid (P) may contain a tetracarboxylic dianhydride or its derivative other than that of the above formula (T).
[0049] The polyamic acid (P) is produced by reacting the diamine component and the tetracarboxylic acid component in a solvent (condensation polymerization). The solvent is not particularly limited as long as the produced polymer is soluble in the solvent. Specific examples of the solvent include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, and 1,3-dimethyl-2-imidazolidinone. In addition, when the polymer has high solubility in the solvent, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, or the solvents represented by the following formulas [D-1] to [D-3] can be used.
[0050] [ka] (In formula [D-1], D 1 represents an alkyl group having 1 to 3 carbon atoms, and in formula [D-2], D 2 represents an alkyl group having 1 to 3 carbon atoms, and in formula [D-3], D 3 represents an alkyl group having 1 to 4 carbon atoms.
[0051] These solvents may be used alone or in combination. Furthermore, even if the solvent does not dissolve the polymer, it may be mixed with the above-mentioned solvent to the extent that the produced polymer does not precipitate. When the diamine component and the tetracarboxylic acid component are reacted in a solvent, the reaction can be carried out at any concentration, but the concentration of the diamine component and the tetracarboxylic acid component in the solvent is preferably 1 to 50% by mass, more preferably 5 to 30% by mass. The reaction can be carried out at a high concentration in the early stage of the reaction, and then the solvent can be added. In the reaction, the ratio of the total number of moles of the diamine components to the total number of moles of the tetracarboxylic acid components (total number of moles of the diamine components / total number of moles of the tetracarboxylic acid components) is preferably 0.8 to 1.2. As in the case of a normal polycondensation reaction, the closer this molar ratio is to 1.0, the higher the molecular weight of the specific polymer produced.
[0052] The polyamic acid ester, which is a polyimide precursor, can be obtained by a known method such as, for example, [I] a method of reacting the polyamic acid obtained by the above synthesis reaction with an esterifying agent, [II] a method of reacting a tetracarboxylic acid diester with a diamine, or [III] a method of reacting a tetracarboxylic acid diester dihalide with a diamine.
[0053] [Polyimide] The polyimide contained in the liquid crystal alignment agent of the present invention is a polyimide obtained by ring-closing the above-mentioned polyimide precursor. In the polyimide, the ring-closing rate of the amic acid group (also called the imidization rate) does not necessarily have to be 100% and can be arbitrarily adjusted according to the application or purpose.
[0054] Methods for obtaining polyimide by imidizing a polyimide precursor include thermal imidization in which a solution of the polyimide precursor is heated as is, and catalytic imidization in which a catalyst is added to a solution of the polyimide precursor. When thermally imidizing a polyimide precursor in a solution, the temperature is 100 to 400°C, preferably 120 to 250°C, and it is preferable to carry out the thermal imidization while removing water generated by the imidization reaction from the system.
[0055] The catalytic imidization of the polyimide precursor can be carried out by adding a basic catalyst and an acid anhydride to a solution of the polyimide precursor and stirring at -20 to 250°C, preferably 0 to 180°C. The amount of the basic catalyst is 0.5 to 30 times by mole, preferably 2 to 20 times by mole, the amount of the acid anhydride is 1 to 50 times by mole, preferably 3 to 3 ...
[0056] When recovering the polyimide produced from the reaction solution of imidization of the polyimide precursor, the reaction solution may be poured into a solvent to cause precipitation. Examples of the solvent used for precipitation include methanol, ethanol, isopropyl alcohol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, toluene, benzene, and water. The polymer precipitated by pouring into the solvent can be recovered by filtration, and then dried at room temperature or by heating under normal or reduced pressure. In addition, the polymer precipitated and recovered can be redissolved in a solvent and the reprecipitation and recovery operation can be repeated 2 to 10 times to reduce impurities in the polymer. Examples of the solvent in this case include alcohols and ketones, and the like. It is preferable to use three or more solvents selected from these because the efficiency of purification is further improved.
[0057] The polystyrene-equivalent weight average molecular weight (Mw) of the polyimide precursor and polyimide measured by gel permeation chromatography (GPC) is preferably 1,000 to 500,000, more preferably 2,000 to 300,000. The molecular weight distribution (Mw / Mn), which is expressed as the ratio of Mw to the polystyrene-equivalent number average molecular weight (Mn) measured by GPC, is preferably 15 or less, more preferably 10 or less. With the molecular weight in this range, good alignment properties of liquid crystal display elements can be ensured.
[0058] (Liquid crystal alignment agent) The liquid crystal aligning agent of the present invention is a liquid composition obtained by dispersing or dissolving the polymer (P) and other components used as necessary, preferably in a suitable solvent.
[0059] In the liquid crystal aligning agent of the present invention, other polymers (hereinafter also referred to as other polymers) may be contained in addition to the polymer (P) for the purpose of improving, for example, electrical properties, vertical alignment properties, and solution properties. Specific examples of other polymers may include, in addition to the polymer (P), at least one polymer selected from the group consisting of polyimide precursors obtained by using a diamine component containing at least one diamine selected from the group consisting of structures represented by the above formulas (S1) to (S3) and polyimides which are imidized products of the polyimide precursors, from the viewpoint of improving vertical alignment properties. The content of the other polymers is preferably 90 parts by mass or less, more preferably 10 to 90 parts by mass, and further preferably 20 to 80 parts by mass, based on 100 parts by mass of the total of the polymers contained in the liquid crystal alignment agent.
[0060] The other polymer is not particularly limited, and examples thereof include the main skeleton of polyimide precursor, polyimide, polysiloxane, polyester, polyamide, cellulose derivative, polyacetal, polystyrene derivative, poly(styrene-phenylmaleimide) derivative, poly(meth)acrylate, etc. Among them, at least one selected from the group consisting of polyimide precursor, polyimide, polyamide, polyorganosiloxane, poly(meth)acrylate, and polyester is preferable. Among them, at least one selected from the group consisting of polyimide precursor, polyimide, and polysiloxane is more preferable. It is to be noted that two or more of the other polymers may be used in combination.
[0061] The liquid crystal aligning agent of the present invention may contain other components as necessary. Examples of the components include at least one compound selected from the group consisting of crosslinkable compounds having at least one substituent selected from epoxy groups, isocyanate groups, oxetanyl groups, cyclocarbonate groups, blocked isocyanate groups, hydroxyl groups, and alkoxy groups, and crosslinkable compounds having polymerizable unsaturated groups, functional silane compounds, metal chelate compounds, curing accelerators, surfactants, antioxidants, sensitizers, preservatives, and compounds for adjusting the dielectric constant and electrical resistance of the liquid crystal alignment film. Preferred specific examples of the crosslinkable compound include compounds represented by the following formulas (CL-1) to (CL-11). Compounds for adjusting the dielectric constant and electrical resistance of the liquid crystal alignment film include monoamines having a nitrogen-containing aromatic heterocycle, such as 3-picolylamine. [ka]
[0062] Examples of the organic solvent used in the liquid crystal aligning agent of the present invention include N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-ethyl-2-pyrrolidone, N-(n-propyl)-2-pyrrolidone, N-isopropyl-2-pyrrolidone, N-(n-butyl)-2-pyrrolidone, N-(tert-butyl)-2-pyrrolidone, N-(n-pentyl)-2-pyrrolidone, N-methoxypropyl-2-pyrrolidone, N-ethoxyethyl-2-pyrrolidone, N-methoxybutyl-2-pyrrolidone, and N-cyclohexyl-2-pyrrolidone. , 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, propyl 3-methoxypropionate, butyl 3-methoxypropionate, ethylene glycol monomethyl ether Examples of the ethylene glycol monomethyl ether include ethylene glycol monoethyl ether, ethylene glycol-n-propyl ether, ethylene glycol-i-propyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol dimethyl ether, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether, propylene glycol monobutyl ether, propylene glycol diacetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol monomethyl ether, dipropylene glycol dimethyl ether, diisobutyl carbinol (2,6-dimethyl-4-heptanol), diisobutyl ketone, isoamyl propionate, isoamyl isobutyrate, diisopentyl ether, ethylene carbonate, and propylene carbonate. These can be used in a mixture of two or more kinds.
[0063] The solid content concentration in the liquid crystal alignment agent (the ratio of the total mass of the components other than the solvent of the liquid crystal alignment agent to the total mass of the liquid crystal alignment agent) is appropriately selected in consideration of viscosity, volatility, etc., and is preferably in the range of 1 to 10 mass%. From the viewpoint of forming a uniform and defect-free coating film, 1 mass% or more is preferable, and from the viewpoint of storage stability of the solution, 10 mass% or less is preferable. A particularly preferable polymer concentration is 2 to 8 mass%.
[0064] <Liquid crystal alignment film> The liquid crystal alignment film for vertical alignment using the liquid crystal alignment agent of the present invention can be produced by sequentially carrying out the steps of applying the liquid crystal alignment agent on a substrate, drying and baking. The substrate used in this case is not particularly limited as long as it is a highly transparent substrate, and in addition to a glass substrate, a plastic substrate such as an acrylic substrate or a polycarbonate substrate can also be used. From the viewpoint of simplifying the process, it is preferable to use a substrate on which an ITO electrode for driving liquid crystal is formed. In addition, in a reflective liquid crystal display element, an opaque substrate such as a silicon wafer can be used for only one substrate, and in this case, a light-reflecting material such as aluminum can also be used for the electrode.
[0065] Examples of methods for applying the liquid crystal alignment agent include screen printing, offset printing, flexographic printing, inkjet method, dip method, roll coater method, slit coater method, spinner method, and spray method. From the viewpoint of improving the production efficiency of the liquid crystal alignment film, the application method by flexographic printing or inkjet method is preferred.
[0066] After the liquid crystal alignment agent is applied onto the substrate, it is dried by a heating means such as a hot plate, a heat circulation oven, or an IR (infrared) oven, preferably at 40 to 150°C depending on the solvent used in the liquid crystal alignment agent, and then baked at a temperature of preferably 150 to 300°C, more preferably 180 to 250°C, to form a liquid crystal alignment film.
[0067] The thickness of the liquid crystal alignment film after baking is preferably 5 to 300 nm, more preferably 10 to 100 nm, since if it is too thick, it is disadvantageous in terms of power consumption of the liquid crystal display element, and if it is too thin, the reliability of the liquid crystal display element may decrease.
[0068] <Liquid crystal display element> The liquid crystal display element of the present invention comprises the above-mentioned liquid crystal alignment film. In a VA mode liquid crystal display element, the coating film formed as described above can be used as it is as a liquid crystal alignment film, but may be subjected to a rubbing treatment or a PSA treatment described later, if necessary.
[0069] The liquid crystal aligning agent of the present invention is also preferably used for a liquid crystal display element manufactured through a process in which a liquid crystal layer is provided between a pair of substrates equipped with electrodes, a liquid crystal composition containing a polymerizable compound that is polymerized by at least one of active energy rays and heat is placed between the pair of substrates, and the polymerizable compound is polymerized by at least one of irradiation with active energy rays and heating while applying a voltage between the electrodes. Here, the voltage applied can be, for example, a direct current or alternating current of 5 to 50 V. Moreover, ultraviolet rays are suitable as the active energy rays. The ultraviolet rays include ultraviolet rays having a wavelength of 300 to 400 nm, preferably ultraviolet rays having a wavelength of 310 to 360 nm. The amount of light irradiation is preferably 0.1 to 20 J / cm. 2 and more preferably 1 to 20 J / cm 2 It is.
[0070] A method for manufacturing a liquid crystal display element using the liquid crystal alignment agent of the present invention includes, for example, a method in which the liquid crystal alignment agent is applied to a pair of substrates having conductive films to form coating films, the coating films are arranged facing each other with a layer of liquid crystal molecules interposed therebetween to form a liquid crystal cell, and the liquid crystal cell is irradiated with light while a voltage is applied between the conductive films of the pair of substrates.
[0071] The above liquid crystal display element controls the pretilt of liquid crystal molecules by the PSA (Polymer Sustained Alignment) method. In the PSA method, a small amount of photopolymerizable compound, for example, photopolymerizable monomer, is mixed into the liquid crystal material, and after assembling a liquid crystal cell, the photopolymerizable compound is irradiated with ultraviolet light or the like while a predetermined voltage is applied to the liquid crystal layer, and the pretilt of the liquid crystal molecules is controlled by the generated polymer. Since the alignment state of the liquid crystal molecules when the polymer is generated is stored even after the voltage is removed, the pretilt of the liquid crystal molecules can be adjusted by controlling the electric field formed in the liquid crystal layer. In addition, the PSA method does not require a rubbing process, so it is suitable for forming a vertical alignment type liquid crystal layer in which it is difficult to control the pretilt by a rubbing process.
[0072] The liquid crystal display element of the present invention is obtained by obtaining a substrate with a liquid crystal alignment film from the liquid crystal aligning agent of the present invention by the above-mentioned method, and then producing a liquid crystal cell by a known method to obtain a liquid crystal display element. Examples of methods for producing a liquid crystal cell include a method of preparing a pair of substrates each having a liquid crystal alignment film formed thereon, spraying spacers onto the liquid crystal alignment film of one of the substrates, bonding the other substrate to the other substrate with the liquid crystal alignment film surface facing inward, and injecting liquid crystal under reduced pressure to seal the cell, and a method of dropping liquid crystal onto the liquid crystal alignment film surface on which the spacers have been sprayed, and then bonding the substrates together to seal the cell.
[0073] As described above, the liquid crystal may be mixed with a polymerizable compound that is polymerized by ultraviolet irradiation or heat. Examples of the polymerizable compound include compounds having one or more polymerizable unsaturated groups, such as acrylate groups or methacrylate groups, in the molecule, such as the polymerizable compounds represented by the following formulas (M-1) to (M-3).
[0074] [ka]
[0075] In this case, the content of the polymerizable compound is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the liquid crystal component. If the content of the polymerizable compound is less than 0.01 part by mass, the polymerizable compound does not polymerize and the alignment of the liquid crystal cannot be controlled, and if it is more than 10 parts by mass, the amount of unreacted polymerizable compound increases, and the image sticking characteristic of the liquid crystal display element decreases. After the liquid crystal cell is produced, the polymerizable compound is polymerized by applying heat or ultraviolet light to the liquid crystal cell while applying an AC / DC voltage to the liquid crystal cell. This makes it possible to control the alignment of the liquid crystal molecules.
[0076] The liquid crystal alignment agent of the present invention may also be used in a liquid crystal display element, i.e., an SC-PVA mode, which is manufactured by a process of having a liquid crystal layer between a pair of substrates equipped with electrodes, disposing a liquid crystal alignment film containing a polymerizable group that is polymerized by at least one of active energy rays and heat between the pair of substrates, and applying a voltage between the electrodes. Here, ultraviolet rays are suitable as the active energy rays. As the ultraviolet rays, the ultraviolet rays used in the PSA method can be used, including the preferred embodiment. In the case of polymerization by heating, the heating temperature is 40 to 120°C, preferably 60 to 80°C. Moreover, ultraviolet rays and heating may be performed simultaneously.
[0077] In order to obtain a liquid crystal alignment film containing a polymerizable group that is polymerized by at least one of active energy rays and heat, a method of adding a compound containing this polymerizable group to a liquid crystal alignment agent, or a method of using a polymer component containing a polymerizable group can be mentioned. A specific example of a polymer containing a polymerizable group is a polymer obtained by using the above-mentioned diamine having a function of being polymerized by irradiation with light. EXAMPLES
[0078] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. In the following, the abbreviations of compounds and the measurement methods of each property are as follows. Furthermore, unless otherwise specified, the numerical values are based on mass.
[0079] <Specific diamine> [ka]
[0080] <Diamine(s)> [ka]
[0081] <Other diamines> [ka] (Boc represents a tert-butoxycarbonyl group.)
[0082] (Tetracarboxylic acid dianhydride) [ka]
[0083] (Organic solvent) NMP: N-methyl-2-pyrrolidone, BCS: Butyl cellosolve THF: Tetrahydrofuran
[0084] [viscosity] The viscosity of the polyamic acid solution was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample amount of 1.1 mL (milliliters), a cone rotor TE-1 (1°34', R24), and a temperature of 25°C.
[0085] [Molecular weight measurement] The molecular weights of the polyimide precursor and polyimide were measured using a room temperature gel permeation chromatography (GPC) apparatus (GPC-101) (manufactured by Showa Denko K.K.) and columns (KD-803, KD-805) (manufactured by Shodex K.K.) as follows. Column temperature: 50℃ Eluent: N,N-dimethylformamide (with lithium bromide monohydrate (LiBr H 2o) is 30mmol / L (liter), phosphoric acid anhydrous crystals (o-phosphoric acid) is 30mmol / L, and tetrahydrofuran (THF) is 10ml / L) Flow rate: 1.0ml / min Standard samples for preparing a calibration curve: TSK standard polyethylene oxide (molecular weight: approximately 900,000, 150,000, 100,000, and 30,000) (manufactured by Tosoh Corporation) and polyethylene glycol (molecular weight: approximately 12,000, 4,000, and 1,000) (manufactured by Polymer Laboratory Co., Ltd.).
[0086] [Measurement of imidization rate] 20 mg of polyimide powder was placed in an NMR (nuclear magnetic resonance) sample tube (NMR sampling tube standard, φ5 (Kusano Scientific Co., Ltd.)), deuterated dimethyl sulfoxide (DMSO-d6, 0.05 mass% TMS (tetramethylsilane) mixture) (0.53 ml) was added, and ultrasonic waves were applied to completely dissolve the powder. This solution was measured by 500 MHz proton NMR using an NMR measurement device (JNW-ECA500) (JEOL Datum Co., Ltd.). The imidization rate was calculated by the following formula using the proton peak integrated value of this proton and the proton peak integrated value of the proton peak derived from the NH group of the amic acid that appears around 9.5 to 10.0 ppm. Imidization rate (%) = (1-α·x / y) × 100 In the above formula, x is the integrated value of the proton peak derived from the NH group of the amic acid, y is the integrated value of the peak of the reference proton, and α is the ratio of the number of reference protons to one NH group proton of the amic acid in the case of polyamic acid (imidization rate 0%).
[0087] <Synthesis example of compound [DA-n-2]> Compound [DA-n-2] was synthesized according to the following scheme. [ka]
[0088] (Synthesis of compound [1]) 6-Bromonaphthalene-2-ol (150g, 672mmol) was added to dimethylformamide (1050g) and cooled under ice cooling. Sodium hydride (60%, 29.6g) was added little by little and stirred under ice cooling for 1 hour, then benzyl bromide (121g) was added and stirred at room temperature for 1 hour. Furthermore, pure water (750g) was added little by little under water cooling and stirred to precipitate crystals, filtered, the filtered cake was slurry washed with methanol (750g), filtered, and the filtered cake was dried to obtain compound [1] (yield: 207g, yield: 98%, white crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):8.13(d,1H,J=2.0Hz),7.85(d,1H,J=9.2Hz),7.78(d,1H,J=8.8Hz),7.58(dd,1H,J=8.8Hz,2.4 Hz),7.53-7.48(m,3H),7.44-7.40(m,2H),7.38-7.33(m,1H),7.30(dd,1H,J=9.0Hz,2.6Hz),5.22(s,2H).
[0089] (Synthesis of compound [2]) Sodium tert-butoxide (82.6 g) and benzophenone imine (126 g) were added to tetrahydrofuran (1000 g) and stirred at room temperature for 30 minutes. 2 (dba) 3(Tris(dibenzylideneacetone)dipalladium(0), 3.03 g) and BINAP (2,2'-bis(diphenylphosphino)-1,1'-binaphthyl, 6.17 g) were added, and the mixture was stirred at 65°C for 23 hours under a nitrogen atmosphere. After cooling to room temperature, 1N hydrochloric acid (1000 g) was added, and the mixture was stirred at room temperature for 15 minutes, and the aqueous layer was separated. Ethyl acetate (200 g), hexane (100 g) and 1N hydrochloric acid (500 g) were further added to the organic layer, and the mixture was added to the separated aqueous layer. Under water cooling, sodium hydroxide (80 g) was added to make the mixture alkaline. The organic layer was separated and washed with a saturated aqueous sodium chloride solution, then dried over sodium sulfate, filtered, and the filtrate was concentrated to obtain a crude product (154 g). Ethyl acetate (462 g) was added to the crude product, which was then dissolved by heating at 70°C, and hexane (770 g) was added and cooled. The mixture was then filtered and the residue was dried to obtain compound [2] (yield: 124 g, yield: 74%, light brown crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):7.50-7.43(m,4H),7.42-7.37(m,2H),7.35-7.30(m,1H),7.19(d,1H,J=2.8Hz),7.0 4(dd,1H,J=8.8Hz,2.8Hz),6.90(dd,1H,J=8.8Hz,2.0Hz),6.80(d,1H,J=2.0Hz),5.13(br,4H).
[0090] (Synthesis of compound [3]) Compound [2] (124 g, 497 mmol) and di-tert-butyl dicarbonate (130 g) were added to dichloromethane (1000 g) and stirred at room temperature for 20 hours. Since the reaction was not completed, di-tert-butyl dicarbonate (10 g) was added and stirred at room temperature for another 20 hours. Saturated aqueous sodium bicarbonate solution (1 L) and dichloromethane (300 g) were added and separated. The organic layer was washed with pure water (450 mL) and saturated aqueous sodium chloride solution (300 mL) in that order, dried over sodium sulfate, filtered, and the filtrate was concentrated to obtain a crude product (198 g). Ethyl acetate (600 g) was added to the crude product and heated to 70 ° C. to dissolve it, then hexane (1000 g) was added and cooled. Then, this was filtered and the filtrate was dried to obtain compound [3] (yield: 142 g, yield: 82%, white crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):9.46(s,1H),8.02(s,1H),7.69(t,2H,J=8.6Hz),7.52-7.49(m,2H),7.45(dd,1H,J=9.0Hz,2 .2Hz),7.43-7.39(m,2H),7.37-7.32(m,2H),7.17(dd,1H,J=9.0Hz,2.6Hz),5.18(s,2H),1.50(s,9H).
[0091] (Synthesis of compound [4]) Compound [3] (122 g, 349 mmol) and 5% palladium carbon (12.2 g) were added to ethanol (976 g) and stirred under a hydrogen atmosphere at 40° C. for 96 hours. The 5% palladium carbon was filtered off, and the filtrate was concentrated to obtain compound [4] (yield: 89.3 g, yield: 99%, white crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):9.52(s,1H),9.37(s,1H),7.94(s,1H),7.62-7.59(m,1H),7.56(d, 1H,J=9.2Hz),7.39(dd,1H,J=9.0Hz,2.2Hz),7.04-7.00(m,2H),1.50(s,9H).
[0092] (Synthesis of compound [5]) 4-Chloronitrobenzene (100g, 635mmol), ethylene glycol (551g) and sodium hydroxide (23.1g) were added to dimethyl sulfoxide (500g) and stirred at 100℃ for 19 hours. After cooling to room temperature, ethyl acetate (560g) and pure water (700g) were added and the mixture was separated. The upper layer was collected, and ethyl acetate (300g) was added to the lower layer and separated, and the upper layers were combined. Pure water (400g) and saturated aqueous sodium chloride solution (200g) were added to the combined upper layers and the mixture was separated again. The ethyl acetate layer was dried over sodium sulfate, filtered, and the filtrate was concentrated to obtain a crude product (110g). Ethyl acetate (330g) was added to the crude product and dissolved by heating at 60℃, and then hexane (550g) was added and cooled. The product was then filtered and the residue was dried to obtain compound [5] (yield: 64.2g, yield: 55%, pale yellow crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):8.21(d,2H,J=9.4Hz),7.16(d,2H,J=9.4Hz),4.97(t,1H,J=5.6Hz),4.15(t,2H,J=4.8Hz),3.77-3.73(m,2H).
[0093] (Synthesis of compound [6]) Compound [5] (63.2 g, 345 mmol) was added to dichloromethane (1264 g) and cooled under ice cooling. Triethylamine (52.4 g), tosyl chloride (69.0 g) and 4-dimethylaminopyridine (1.26 g) were added to the mixture and stirred at room temperature for 19 hours. Pure water (632 g) was added, and the mixture was separated to recover the dichloromethane layer, which was then washed with 1N hydrochloric acid (300 g), pure water (300 g), and saturated aqueous sodium chloride solution (300 g) in that order, dried over anhydrous sodium sulfate, filtered, and the filtrate was concentrated to obtain compound [6] (yield: 108 g, yield: 93%, white crystals). 1 H-NMR (400MHz, DMSO-d 6,δ(ppm)):8.18(d,2H,J=9.2Hz),7.80(d,2H,J=8.6Hz),7.47(d,2H,J=8.6Hz ),7.05(d,2H,J=9.2Hz),4.40-4.37(m,2H),4.35-4.31(m,2H),2.41(s,3H).
[0094] (Synthesis of compound [7]) Compound [4] (45.0 g, 174 mmol), compound [6] (61.5 g) and potassium carbonate (36.0 g) were added to dimethylformamide (360 g) and stirred at 80°C for 21 hours. After cooling to room temperature, pure water (720 g) was added to precipitate crystals. After filtration, the residue was slurry washed with methanol (360 g), filtered, and dried to obtain compound [7] (yield: 67.2 g, yield: 91%, pale ochre crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):9.47(s,1H),8.23(d,2H,J=9.2Hz),8.02(s,1H),7.72-7.69(m,2H),7.46(dd,1H,J=8.8Hz,2.0Hz),7.31(d, 1H,J=2.4Hz),7.24(d,2H,J=9.2Hz),7.14(dd,1H,J=9.0Hz,2.6Hz),4.56-4.53(m,2H),4.46-4.43(m,2H),1.50(s,9H).
[0095] (Synthesis of compound [8]) Compound [7] (73.1 g, 172 mmol) was added to chloroform (1096 g), and trifluoroacetic acid (98.1 g) was added while stirring under water cooling, and the mixture was stirred at 50 ° C for 19 hours. After cooling to room temperature, triethylamine (87.0 g) and pure water (1096 g) were added to precipitate crystals. After filtration, the residue was slurry washed with methanol (365 g), filtered, and dried to obtain a crude product (49.5 g). Dimethylformamide (124 g) was added to the crude product, and the mixture was dissolved by heating at 80 ° C, and then methanol (248 g) was added and cooled to precipitate crystals. After filtration and drying the residue, compound [8] was obtained (yield: 47.3 g, yield: 85%, orange crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):8.23(d,2H,J=9.2Hz),7.51(dd,1H,J=8.8Hz,2.4Hz),7.45(dd,1H,J=8.8Hz,2.4Hz),7.24(dd,2H,J=9.2Hz,2.4Hz) ,7.27(s,1H),7.01(d,1H,J=9.2Hz),6.91(d,1H,J=8.8Hz),6.80(s,1H),5.15(br,2H),4.55-4.51(m,2H),4.41-4.37(m,2H).
[0096] (Synthesis of compound [DA-n-2]) Compound [8] (46.4 g, 143 mmol) and 5% palladium carbon (4.6 g) were added to dimethylformamide (371 g) and stirred at 60° C. under a hydrogen atmosphere for 19 hours. Since the reaction did not proceed much, the mixture was stirred at 60° C. for 8 hours in an autoclave under a 0.4 MPa hydrogen atmosphere. After nitrogen replacement, the 5% palladium carbon was filtered, and the filtrate was concentrated to an amount of 80 g. Dimethylformamide (46 g) was added, and the mixture was dissolved by heating at 90° C., and then methanol (210 g) was added and cooled to precipitate crystals. The mixture was then filtered and the residue was dried to obtain compound [DA-n-2] (yield: 33.4 g, yield: 79%, pale purple crystals). 1 H-NMR (400MHz, DMSO-d 6,δ(ppm)):7.50(d,1H,J=8.8Hz),7.44(d,1H,J=8.8Hz),7.13(d,1H,J=2.8Hz),7.00(dd,1H,J=8.8Hz,2.8Hz),6.90(dd,1H,J=8.8Hz,2.4H z),6.79(d,1H,J=2.4Hz),6.71(d,2H,J=8.8Hz),6.52(d,2H,J=8.8Hz),5.13(br,2H),4.63(br,2H),4.28-4.25(m,2H),4.20-4.17(m,2H).
[0097] <Synthesis of compound [DA-n-3]> Compound [DA-n-3] was synthesized according to the following scheme.
[0098] [ka]
[0099] (Synthesis of compound [9]) In a four-neck flask, 6-bromo-2-naphthaleneamine (30.0 g, 135 mmol), tetrahydrofuran (450 g), (4-nitrophenyl)boronic acid (27.2 g, 163 mmol), methanol (300 g), cesium carbonate (132 g, 405 mmol), and water (150 g) were charged and purged with nitrogen. Tetrakis(triphenylphosphine)palladium(0) (3.12 g, 2.70 mmol) was added thereto, purged with nitrogen, and stirred overnight at 55°C. After completion of the reaction, the reaction solution was added to water (750 g) to precipitate crystals, which were then filtered and collected. Isopropyl alcohol (216 g) was added to the obtained crystals, which were heated and stirred at 65°C, and toluene (300 g) was added while cooling to room temperature to precipitate them. This was filtered, the cake was washed with toluene and hexane, and the crystals were dried to obtain compound [9] (yield: 28.0 g, 106 mmol, 78%). 1 H-NMR (500MHz, DMSO-d 6,δ(ppm)):8.30(d,J=8.5Hz,2H),8.13(s,1H),8.03(d,J=8.6Hz,2H),7.72(d,J=8 .8Hz,2H),7.63(d,J=8.7Hz,1H),7.00(d,J=8.5Hz,1H),6.85(s,1H),5.63(s,2H).
[0100] (Synthesis of compound [DA-n-3]) Compound [9] (28.0g, 106mmol) was mixed with N,N-dimethylformamide (224g) and substituted with nitrogen, then 5% palladium carbon (wet product, 2.24g) was added and substituted with nitrogen, and a hydrogen Tedlar bag was attached and stirred at room temperature overnight. After the reaction was completed, the palladium carbon was removed by passing through a membrane filter, and the filtrate was added to water (248g) to precipitate crystals, filtered, and the crystals (wet) were collected. Isopropyl alcohol (50g) was added to the obtained crystals, heated and stirred at 55℃, and toluene (74g) was added while cooling to room temperature to crystallize. The crystals were collected by filtration (crystal A). The filtrate was concentrated and crystallized again with isopropyl alcohol (55℃)-toluene (room temperature), filtered, and the crystals were collected (crystal B). The obtained crystals A and B were dried to obtain compound [DA-n-3]. (Yield: 17.6g, 75.1mmol, 71% yield) 1 H-NMR (500MHz, DMSO-d 6 ,δ(ppm)):7.76(s,1H),7.60(d,J=8.7Hz,1H),7.53-7.49(m,2H),7.41(d,J=8.2 Hz,2H),6.92(d,J=8.7Hz,1H),6.80(s,1H),6.66(d,J=8.2Hz,2H),5.25(s,4H).
[0101] <Synthesis example of compound [DA-n-9]> Compound [DA-n-9] was synthesized according to the following scheme.
[0102] [ka]
[0103] (Synthesis of compound [4]) Compound [4], a synthetic intermediate in [DA-n-2], was used. (Synthesis of compound
[10] ) Ethylene glycol ditosylate (60.7g, 164mmol), compound [4] (89.3g) and potassium carbonate (56.7g) were added to dimethylformamide (607g) and stirred at 80°C for 22 hours. After cooling to room temperature, pure water (1200g) was added to precipitate crystals. Then, it was filtered, the filter cake was slurry washed with methanol (450g), filtered, and the filter cake was dried to obtain a crude product (83.9g). Dimethylformamide (839g) was added to the crude product, and it was dissolved by heating at 90°C, and then methanol (839g) was added and cooled to precipitate crystals. Then, it was filtered, and the filter cake was dried to obtain compound
[10] (yield: 71.2g, yield: 80%, orange crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):9.43(s,2H),7.99(br,2H),7.67(d,4H,J=8.8Hz),7.43(dd,2H,J=8.8Hz,2. 4Hz),7.28(d,2H,J=2.4Hz),7.12(dd,2H,J=8.8Hz,2.4Hz),4.42(s,4H),1.47(s,18H).
[0104] (Synthesis of compound [DA-n-9]) Compound
[10] (71.2 g, 129 mmol) was added to chloroform (1143 g) and cooled under water cooling. Trifluoroacetic acid (160 g) was added to the mixture and stirred at 50° C. for 24 hours. After cooling to room temperature, triethylamine (142 g) and pure water (1143 g) were added to precipitate crystals. Then, the mixture was filtered, the residue was slurry washed with methanol (400 g), filtered, and the residue was dried to obtain a crude product (37.5 g). Dimethylformamide (225 g) was added to the crude product, and the mixture was dissolved by heating at 90° C., and then methanol (225 g) was added and cooled to precipitate crystals. The mixture was filtered and the residue was dried to obtain compound DA-n-9 (yield: 33.5 g, yield: 75%, pale red-purple crystals). 1 H-NMR (400MHz, DMSO-d 6 ,δ(ppm)):7.51(d,2H,J=8.8Hz),7.45(d,2H,J=8.8Hz),7.17(d,2H,J=2.4Hz),7.02(dd,2H,J=8 .8Hz,2.4Hz),6.91(dd,2H,J=8.8Hz,2.4Hz),6.80(d,2H,J=2.4Hz),5.14(br,4H),4.37(s,4H).
[0105] <Synthesis example of compound [DA-n-10]> Compound [DA-n-10] was synthesized according to the following scheme.
[0106] [ka]
[0107] (Synthesis of compound
[11] ) tert-Butyl (5-hydroxy-1-naphthalenyl) carbamate (27.0 g, 104 mmol) was charged with N,N-dimethylformamide (216 g) and potassium carbonate (33 g, 239 mmol) and stirred at 80 ° C. Next, a solution of 1,2-bis (4-methylbenzenesulfonate)-1,2-ethanediol (18.0 g, 496 mmol) in N,N-dimethylformamide (162 g) was added dropwise using a dropping funnel, and the mixture was heated and stirred at 80 ° C. overnight. After the reaction was completed, the reaction solution was poured into water (2268 g) to precipitate crystals. The mixture was filtered using a Buchner funnel to obtain sticky black purple crystals (93 g). The crude product was dissolved in N,N-dimethylformamide by heating at 80°C, cooled to room temperature, and crystallized in methanol. The product was filtered and dried to obtain compound
[11] (yield: 28.0 g, 51.4 mmol, 67%). 1 H-NMR (500MHz, DMSO-d 6, δ (ppm)): 9.14 (s, 2H), 7.98 (d, J = 10.0 Hz, 2H), 7.64 (d, J = 10.0 Hz, 2H), 7.55 (d, J = 10.0 Hz, 2H), 7.46 (t, J = 7.5 Hz, 2H), 7.39 (t, J = 7.5 Hz, 2H), 7.13 (d, J = 10.0 Hz, 2H), 4.65 (s, 4H), 1.49 (s, 18H).
[0108] (Synthesis of Compound [DA-n-10]) To compound
[11] (28.0 g, 51.4 mmol), chloroform (374 g) and potassium carbonate (33 g, 239 mmol) were charged and stirred at 80 °C. Next, trifluoroacetic acid (31.0 g, 313 mmol) was slowly added dropwise through a dropping funnel, and the mixture was heated and stirred at 50 °C for 6 hours. As a result, gray crystals precipitated in the reaction system. After cooling to 25 °C, the reaction solution was poured into water (374 g) and filtered. To the obtained crystals, triethylamine and water were added and stirred to liberate the diamine from the trifluoroacetate salt. After filtration again, the crystals were washed with methanol and then hexane, and dried to obtain compound [DA-n-10] (yield: 9.30 g, 27.0 mmol, 86% yield). 1 1H-NMR (500 MHz, DMSO-d 6 , δ (ppm)): 7.65 (d, J = 7.5 Hz, 2H), 7.41 (d, J = 8.0 Hz, 2H), 7.29 (t, J = 8.0 Hz, 2H), 7.12 (t, J = 8.0 Hz, 2H), 7.00 (t, J = 7.5 Hz, 2H), 6.67 (d, J = 7.5 Hz, 2H), 5.62 (s, 4H), 4.56 (s, 4H).
[0109] (Synthesis of DA-v-7) Compound [DA-v-7] was synthesized according to the following scheme. "MeO" represents a methoxy group. [Chemical formula]
[0110] (Synthesis of Compound 3 (3a, 3b mixture)) Magnesium (15.39 g, 63.3 mmol, 1.5 eq.) was added to a four-neck flask, and the mixture was vacuum-dried for 1 hour using a vacuum pump. THF (100 g) was then added using a syringe and stirred at room temperature. Next, a solution of compound 1 (100 g, 42.2 mmol) in THF (300 g) was gradually added dropwise at a rate of gentle reflux. The reaction solution was then cooled to 0°C, and a solution of compound 2 (105.60 g, 42.2 mmol, 1.0 eq.) in THF (200 g) was added dropwise. After the dropwise addition was completed, the temperature of the reaction solution was returned to room temperature, and the mixture was stirred at room temperature for 3 hours. Then, toluene (1 L) was added to dilute the reaction solution, and the reaction solution was cooled again to 0°C, and 10% acetic acid solution (500 g) was gradually added dropwise. Next, the aqueous layer was removed by a separation operation, and the organic layer was washed with saturated saline (1 L), saturated aqueous sodium bicarbonate solution (1 L), and saturated saline (1 L), respectively, and dried over anhydrous magnesium sulfate. Then, filtration and distillation were performed using an evaporator to obtain 172 g of crude crystals of compound 3. The obtained crude crystals were used as they were in the next reaction.
[0111] (Synthesis of compound 4) A mixture of crude crystals of compound 3 (172 g, 422 mmol), p-toluenesulfonic acid monohydrate (4.82 g, and 25.3 mmol, 0.06 eq.) in dehydrated toluene (MS4A dehydrated product, 2 L) was reacted under reflux for 2 hours while removing water. After the reaction was completed, about half of the amount of toluene used was distilled off using an evaporator, and the solution was stirred at room temperature to precipitate a solid. The obtained solid was filtered to obtain crystals of compound 4 (yield 150 g, yield 91%).
[0112] (Synthesis of compound 5 (5a, 5b mixture)) A mixture of compound 4 (108 g, 276 mmol), 5% palladium carbon (wet product, 11 g, 10 wt%), ethyl acetate (1 L), and ethanol (1 L) was stirred at room temperature in the presence of hydrogen. After the reaction was completed, toluene (2 L) was added to dissolve the crystals, and the reaction mixture was filtered through Celite, and the Celite was washed with 1 L of toluene. The filtrate was concentrated under reduced pressure to obtain the target compound 5 (yield: 103.3 g, yield: 95%).
[0113] (Synthesis of compound 6) At 0°C under nitrogen purging, compound 5 (95.4 g, 243 mmol) was dissolved in methylene chloride (800 mL) and BBr 3 (1.0M-CH 2 Cl 2 , 243mL, 1.01mol) was added dropwise. After the addition, the mixture was stirred at 0°C for 2 hours. After the reaction was completed, the reaction solution was added little by little to distilled water. The mixture was extracted with ethyl acetate (1L), and the extract was washed twice with 500mL of distilled water. The organic layer was dried over magnesium sulfate, and the solvent was distilled off under reduced pressure. The obtained crude product was recrystallized with ethanol, filtered, and washed with ethanol to obtain the target compound 6 (yield 18.6g, yield 21%).
[0114] (Synthesis of compound 8) A solution of compound 7 (5.35 g, 26.4 mmol) in toluene (20 g) was added dropwise to a mixture of compound 6 (10.0 g, 26.4 mmol), potassium carbonate (11.0 g, 79.2 mmol, 3 eq.), and toluene (50 g) under reflux. After the addition, the mixture was stirred overnight at reflux. After the reaction was completed, the reaction solution was cooled to about 60°C, ethyl acetate (500 g) was added, and the mixture was washed three times with distilled water. The organic layer was dried over anhydrous magnesium sulfate, and the solvent was distilled off under reduced pressure. The obtained crude product was recrystallized in an acetonitrile / ethanol (2:1) solution, filtered, and the filtered crystals were washed with ethanol to obtain crude crystals of compound 8. The crude crystals were purified by column chromatography (SiO 2 ,CHCl 3 ) to obtain crystals of compound 8 (yield: 7.1 g, yield: 49%).
[0115] (Synthesis of DA-v-7) A mixture of compound 8 (12.2 g, 22.4 mmol), 5% palladium carbon (wet product, 1.22 g, 10 wt%), and 1,4-dioxane (120 g) was stirred in the presence of hydrogen at 60°C for 4 hours. After the reaction was completed, the mixture was purged with nitrogen and filtered through Celite at 60°C. The filtrate was distilled under reduced pressure to remove the solvent, yielding a crude product. The crude product was recrystallized from 2-propanol / ethyl acetate (2:1) to obtain the target product, DA-v-7 (yield 8.0 g, 74%). 1 H-NMR (500MHz, CDCl 3 ,δ(ppm)):7.725(1H,d),7.577(2H,m),7.272(2H,m),7.102(1H,s),6.791(1H,d),6 .207(1H,d),6.117(1H,dd),3.621(4H,broad),2.553(1H,m),2.067-0.863(31H,m).
[0116] [Synthesis of polyamic acid] <Synthesis Example 1> In a 100mL four-neck flask equipped with a stirrer, 1.66g (7.00mmol) of DA-4, 2.89g (8.75mmol) of DA-5, 5.30g (7.00mmol) of DA-v-6, and 2.43g (12.3mmol) of DA-13 were weighed out, and 49.1g of NMP was added and stirred to dissolve. While stirring this diamine solution, 7.53g (33.6mmol) of DC-3 was added, and then 30.1g of NMP was added. The mixture was stirred at 60℃ for 15 hours to obtain a solution of polyamic acid (A-R1, viscosity: 649mPa·s, number average molecular weight: 14,231).
[0117] <Synthesis Examples 2 to 13> Polyamic acid solutions (A-R2) to (A-R9) and (A-B1) to (A-B4) shown in Table 1 were obtained by carrying out the same procedure as in Synthesis Example 1, except that the diamine component and the acid dianhydride component were changed to those shown in Table 1. The viscosity and molecular weight of the obtained polyamic acid are also shown in Table 1.
[0118] [Table 1]
[0119] [Preparation of liquid crystal alignment agent] <Example 1> NMP (6.0 g) and BCS (8.0 g) were added to the solution (6.0 g) of polyamic acid (A-R1) obtained above, and the mixture was stirred at room temperature for 10 hours to obtain a liquid crystal alignment agent (R1) containing 6 mass % of polyamic acid (A-R1), 54 mass % of NMP, and 40 mass % of BCS.
[0120] <Synthesis Examples 2 to 13> Except for using polyamic acids (A-R2) to (A-R9) and (A-B1) to (A-B4) instead of polyamic acid (A-R1), as shown in Table 2 below, the same procedure as in Example 1 was carried out to obtain liquid crystal alignment agents (R2) to (R9) and (B1) to (B4) of Examples 2 to 13, as shown in Table 2 below. In addition, among Examples 1 to 13 in Table 2, Examples 1 to 3 and 6 to 9 are comparative examples, and Examples 4, 5 and 10 to 13 are examples of the present invention.
[0121] [Table 2]
[0122] The solid content ratio in the above Table 2 indicates the content ratio of the polymer solid content relative to 100 parts by mass of the liquid crystal alignment agent, and the solvent composition ratio indicates the content ratio (parts by mass) in each organic solvent.
[0123] <Examples 14-21> The liquid crystal alignment agent (R1) obtained in Example 1 and the liquid crystal alignment agent (R4) obtained in Example 4 were mixed in a mass ratio of 3:7, and stirred at room temperature for 3 hours to prepare the liquid crystal alignment agent (B5) of Example 14. In addition, in Examples 15 to 21, the liquid crystal alignment agents (B6 to B8, R10 to R13) of Examples 15 to 21 were prepared by carrying out the same procedure as in Example 14, except that the combination of the liquid crystal alignment agents used was changed to that shown in Table 3 below. [Table 3]
[0124] <Examples 22-35> Liquid crystal alignment films and liquid crystal cells were prepared as follows, and the properties of each prepared liquid crystal cell were evaluated. The results are shown in Table 4. In the following examples, Examples 22 to 25 and 28 to 31 are examples of the present invention, and Examples 26, 27, and 32 to 35 are comparative examples. [Preparation of liquid crystal alignment film] Using the liquid crystal alignment agents prepared in the above Examples 1 to 21, liquid crystal alignment films were produced as follows: Each liquid crystal alignment agent was spin-coated on a quartz substrate or a silicon wafer, dried on a hot plate at 70°C for 90 seconds, and then baked in a hot air circulation oven (MB1-1G3030X, manufactured by Denko Co., Ltd.) at 230°C for 20 minutes to form a liquid crystal alignment film with a thickness of 100 nm.
[0125] [Measurement of refractive index of liquid crystal alignment film] A spectroscopic ellipsometer (JA Woollam, M-2000) was used to measure the refractive index at wavelengths of 250 to 800 nm by fitting using the CAUCHY model. The results are shown in Table 4. Table 4 also shows the refractive index at a wavelength of 550 nm. A refractive index of more than 1.62 was rated as "good," and a refractive index of 1.62 or less was rated as "poor."
[0126] [Measurement of transmittance of liquid crystal alignment film] A measurement cell was made using two quartz substrates. A liquid crystal alignment film was formed on one of the two substrates, and a quartz substrate without a liquid crystal alignment film was attached to it with the side on which the liquid crystal alignment film was formed facing inward. A refractive index liquid (contact liquid, manufactured by Shimadzu Device Mfg. Co., Ltd.) was inserted between the two substrates using a dropper to make a measurement cell. A refractive index liquid was used according to each of the 11 types of refractive index liquids ranging from 1.60 to 1.70 in 0.01 increments. The transmittance of the measurement cell prepared above was measured at wavelengths of 380 to 800 nm using an ultraviolet-visible spectrophotometer (Shimadzu Corporation, UV-2600). The results are shown in Table 4. Table 4 shows the average transmittance at wavelengths of 380 to 800 nm. A transmittance of more than 99.0% was rated as "good", and a transmittance of 99.0% or less was rated as "poor".
[0127] "Preparation of liquid crystal alignment film and liquid crystal cell" Using the liquid crystal alignment agents prepared in the above respective Examples, liquid crystal cells were produced as follows. Each liquid crystal alignment agent was spin-coated onto the ITO surface of an ITO electrode substrate on which an ITO electrode pattern with a pixel size of 100 μm × 300 μm and a line / space of 5 μm each was formed, and the substrate was dried on a hot plate at 70°C for 90 seconds, and then baked in a hot air circulating oven at 230°C (MB1-1G3030X, manufactured by Denko Corporation) for 30 minutes to form a liquid crystal alignment film with a thickness of 100 nm. In addition, a liquid crystal alignment agent was spin-coated onto the ITO surface on which no electrode pattern was formed, and then dried on a hot plate at 70°C for 90 seconds. After that, it was baked for 20 minutes in a hot air circulating oven at 230°C (MB1-1G3030X, manufactured by Denko Corporation) to form a liquid crystal alignment film with a thickness of 100 nm.
[0128] For the two substrates described above, 4 μm bead spacers were sprayed on the liquid crystal alignment film of one substrate, and then a sealant (solvent-based thermosetting epoxy resin) was printed on top of the bead spacers. Next, the other substrate was attached to the previous substrate with the side on which the liquid crystal alignment film was formed facing inward, and the sealant was cured to prepare an empty cell. Liquid crystal MLC-3023 (product name manufactured by Merck) containing a polymerizable compound was injected into this empty cell by a reduced pressure injection method to prepare a liquid crystal cell.
[0129] After that, with a DC voltage of 15 V applied to the liquid crystal cell, UV light of 10 J / cm2 was applied from the outside of the liquid crystal cell through a filter that cuts wavelengths of 325 nm or less. 2The UV illuminance was measured using an ultraviolet irradiance meter (UV-MO3A manufactured by ORC). After that, in order to inactivate the unreacted polymerizable compound remaining in the liquid crystal cell, the cell was irradiated with UV (UV lamp: FLR40SUV32 / A-1) for 30 minutes using a UV-FL irradiation device (manufactured by Toshiba Lighting & Technology Corporation) in a state where no voltage was applied.
[0130] "Evaluation of Liquid Crystal Cells" The properties of each of the liquid crystal cells prepared as described above were evaluated as follows. (Evaluation of vertical alignment) The liquid crystal cell was sandwiched between crossed Nicol polarizing plates, and the liquid crystal cell was rotated under a backlight irradiated from behind, and the change in brightness was visually observed to see whether the liquid crystal was vertically aligned. The evaluation criteria were as follows: ◯: The liquid crystal is vertically aligned. ×: The liquid crystal is not vertically aligned.
[0131] [Table 4]
[0132] The entire contents of the specification, claims and abstract of Japanese Patent Application No. 2019-173271, filed on September 24, 2019, are hereby incorporated by reference as the disclosure of the specification of the present invention.
Claims
1. Diamines represented by the following formula (DA-n-2), (DA-n-3), (DA-n-9) or (DA-n-10). 【Chemistry 1】
2. A polymer obtained from a diamine component comprising the diamine according to claim 1.
3. A polyimide which is a polyimide precursor obtained by a polycondensation reaction between a diamine component containing the diamine according to claim 1 and a tetracarboxylic acid component, or an imidized product thereof.
Citation Information
Patent Citations
Novel oxidation hairdying coupling agent ingredient*its manufacture and hair dye containing it
JP1980079351A
Liquid crystal display panel and manufacturing method thereof
JP2008076950A
Liquid crystal display device and polymer for aligning film material
WO2008117615A1